2019
DOI: 10.3390/cancers11121981
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Story of Heterogeneous B-raf V600E Mutation Quantitative Protein Expression in Metastatic Melanoma—Association with Clinical Outcome and Tumor Phenotypes

Abstract: In comparison to other human cancer types, malignant melanoma exhibits the greatest amount of heterogeneity. After DNA-based detection of the BRAF V600E mutation in melanoma patients, targeted inhibitor treatment is the current recommendation. This approach, however, does not take the abundance of the therapeutic target, i.e., the B-raf V600E protein, into consideration. As shown by immunohistochemistry, the protein expression profiles of metastatic melanomas clearly reveal the existence of inter- and intra-tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 60 publications
0
23
0
1
Order By: Relevance
“…Such an additive outcome was indeed reported in a previous gene set enrichment study, which demonstrated the downregulation of genes involved in oxidative phosphorylation in the muscle biopsies of human diabetic patients, with an average reduction of 20% per gene [ 64 ]. Since the mRNA levels may not always be reflecting the amount of active proteins [ 65 ], further studies at the protein level would also be invaluable for determining the functional consequences of this altered gene expression profile on the glycogen metabolism with regard to the monosomy-3 status.…”
Section: Discussionmentioning
confidence: 99%
“…Such an additive outcome was indeed reported in a previous gene set enrichment study, which demonstrated the downregulation of genes involved in oxidative phosphorylation in the muscle biopsies of human diabetic patients, with an average reduction of 20% per gene [ 64 ]. Since the mRNA levels may not always be reflecting the amount of active proteins [ 65 ], further studies at the protein level would also be invaluable for determining the functional consequences of this altered gene expression profile on the glycogen metabolism with regard to the monosomy-3 status.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the underlying causes of breast cancer also demonstrates that coupling genomic/transcriptomic data with proteomic/phosphoproteomic analysis was more insightful than any individual approach. Of note, melanoma tumour genomic BRAF driver mutations match corresponding protein sequences 97 , illustrating that proteomic landscapes add value to genomic data, when considered with patient tumour histopathology and clinical metadata 98 .…”
Section: Translating Proteomics To Precision Medicinementioning
confidence: 99%
“…Среди последних исследований в онкологии с привлечением ресурса биобанков следует процитировать передовое исследование по гетерогенности метастатической меланомы в отношении экспрессии гена B-rafV600 и возможности его количественного определения методом масс-спектрометрии в сочетании с секвенированием ДНК и мРНК. Анализ количества белка B-raf позволил выявить отдельные дополнительные группы прогноза ответа на терапию BRAF и MEK-ингибиторами среди пациентов с B-raf-положительной метастатической опухолью [42].…”
Section: исследования в онкологии с привлечением ресурса биобанковunclassified